Stability of the Cournot Process - Experimental Evidence - Steffen Huck; Hans-Theo Normann; Jörg Oechssler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
We report results of experiments designed to test the predictions of the best reply process. In a Cournot oligopoly with four firms, the best reply process should theoretically explode if demand and cost functions are linear. We find, however, no experimental evidence of such instability. Moreover, we find no differences between a market which theoretically should not converge to Nash equilibrium and one which should converge because of inertia. We investigate the power of several learning dynamics to explain this unpredicted stability.
Keywords: C72; C92; L13; 330; best reply process; Cournot oligopoly; learning experiments; imitation